Law Enforcement And Socio-Legal Approaches In Combating Destructive Fishing Crimes In Maluku: Policy Analysis, Implementation Challenges, And Community Empowerment - Sherly Adam; Harly Clifford Jonas Salmon; Astuti Nur Fadilah (PT. Anagata Sembagi Education, 2025)
Destructive fishing is a form of fisheries crime that causes ecological damage and threatens the socio-economic stability of coastal communities. Maluku Province, a strategic archipelagic region highly dependent on marine resources, faces significant challenges in preventing and combating this practice. This study analyzes the enforcement of destructive fishing offenses through normative-juridical and socio-legal approaches by examining national legal frameworks, the effectiveness of the lex specialis principle, institutional enforcement capacity, and socio-economic dynamics and legal culture among coastal communities. The findings reveal that although national legal provisions offer a strong normative foundation, law enforcement in Maluku remains constrained by geographical barriers, limited numbers of specialized fisheries investigators, and insufficient maritime surveillance infrastructure. Additionally, economic pressure, lack of access to sustainable fishing technologies, and low legal awareness contribute to persistent destructive fishing practices. Addressing this issue requires integrating penal instruments with community-based empowerment strategies, including the revitalization of traditional norms such as sasi laut, capacity-building for enforcement officers, technological strengthening of maritime monitoring, and the development of coastal livelihood alternatives. This study concludes that successful mitigation of destructive fishing depends on the synergy between legal policies, community participation, and sustained institutional strengthening.